Protective Role of Vitamin-C and Resveratrol on Spirotetramat Induced Reproductive Toxicity in Male Wistar Rats - Hussain , Shariq; Gaur, Madhavi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The study was aimed to investigate the potential protective effects of Vitamin-C and Resveratrol on reproductive toxicity induced by spirotetramat in male Wistar rats. To evaluate the protective role of Vitamin–C and Resveratrol, six groups of male Wistar rats ; Group-I (Control), Group-II (Toxicity Control-Spirotetramat 667mg/kgbw), Group-III (Treatment control- Vitamin-C 200mg/kgbw+ Resveratrol 20mg/kgbw), Group IV (Treated 1- Spirotetramat + Vitamin-C 200mg/kgbw), Group-V (Treated 2- Spirotetramat + Resveratrol 20mg/kgbw) and Group-VI (Combination) were framed. The groups were administrated by Spirotetramat (667mg/kgbw), Vitamin-C (200 mg/kgbw) and Resveratrol (20mg/kgbw) for 4 weeks as per the prescribed protocol. Spirotetramat induced testicular toxicity by affecting various parameters of reproductive health. Treatments with the Vitamin-C and Resveratrol showed a significant fortification of reproductive system and associated parameters by reducing the ill effects of Spirotetramat thereby enhancing sperm motility and suppressing sperm abnormality. Spirotetramat showed a decline in in Superoxide dismutase (SOD) Reduced Glutathione (GSH) and Catalase (CAT) with elevation in Malondialdehyde (MDA). After Co-administration of Vitamin-C and Resveratrol levels were found to be normalized revealing their potential efficacy against oxidative stress. The results of this study showed that spirotetramat exposure caused significant reductions in sperm count, motility, and viability in male rats. However, treatment with Vitamin-C and Resveratrol was found to mitigate these effects. Specifically, co-treatment with Spirotetramat and Vitamin-C or Resveratrol resulted in significant improvements in sperm count, motility, and viability in male Wistar rats.